Financial Statement Fraud Model: (Case Study on BUMN Companies for the 2021-2022 Period) - Iin Ardi Yanti; Riswan Riswan; Aminah Aminah (Cita konsultindo, 2024)
The fraud problem that occurred at PT Waskita Karya recently became the background of this research. The purpose of this study was to determine the effect of the independent board of commissioners and institutional ownership on financial statement fraud and the role of financial performance in mediating the effect of the independent board of commissioners and institutional ownership on financial statement fraud. A quantitative approach is used in this study with the population, namely BUMN companies, for the 2021–2022 period, and purposive sampling is used to select samples. The number of samples was 17 for a two-year period, so 34 research data points were obtained. The results of this study show that the independent board of commissioners and institutional ownership have a negative and significant effect on financial statement fraud, and financial performance can mediate the effect of independent commissioners and institutional ownership on financial statement fraud. The conclusion of this study indicates that the number of commissioners in the company and the number of shares owned by institutions that can affect financial statement fraud, as well as the amount of supervision from independent commissioners and institutions that invest capital, will have an impact on the better financial performance of the company, and this will reduce the actions of managers to commit financial statement fraud.